Room-temperature polarized spin-photon interface based on a semiconductor nanodisk-in-nanopillar structure driven by few defects - Shula Chen (Nature Portfolio, 2018)
Room-temperature spin-generation in 1D systems like semiconductor nanopillars is typically inefficient. Here, the authors demonstrate an approach to achieve efficient spin polarization, even in the absence of a magnetic field, by selectively enhancing the radiative efficiency of one spin direction.